Barriers or catalysts? Traditional institutions and social mobility in rural India - Vegard Iversen; Anustup Kundu; Rahul Lahoti; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We examine how village-level social group dominance affects the educational and occupational mobility of minority and other social groups in rural India across multiple generations. We distinguish between upper caste and own-group dominance and examine the mechanisms underpinning inequality in mobility outcomes. We find inequality in upward educational mobility to have significantly narrowed over time, with Scheduled Castes doing better in upper caste- and own-dominated villages, while Scheduled Tribes and Muslims do worse in own-dominated villages. In contrast, for occupational mobility we find no evidence of minority groups catching up with upper castes; Scheduled Castes and Scheduled Tribes are particularly disadvantaged, but Scheduled Castes, again, do comparatively better in their own-dominated villages. Exploring the mechanisms that explain the relationships between land dominance regimes and mobility, we find that a combination of agroecological and natural resource base and social cohesion of villages underpins the differences observed more than public goods provision. Our findings suggest a new pattern of inequality where historically disadvantaged groups appear less able to convert educational gains into labour market and occupational progress.
Keywords: J62; J71; O12; 330; educational mobility; occupational mobility; caste; land dominance regimes; India